2008
DOI: 10.1111/j.1438-8677.2008.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Daylength responses of various morphogenetic events after panicle initiation in late japonica rice (Oryza sativa L. ssp. japonica)

Abstract: Plant morphogenesis is an intimate cooperation between environmental signals and a genetically-encoded developmental programme. Although all stages subsequent to floral induction may be influenced by daylength, the information available has come from diverse species during different morphogenetic events. This makes it difficult to investigate how photoperiodic signalling is integrated into various steps of the developmental programme. Here, we report that, in late japonica rice lines, morphogenetic events, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These findings suggested that vegetative growth could proceed relatively well, even when rice plants were grown under short-day conditions at a high temperature if the time of seeding and transplanting of younger seedlings was delayed. Panicle length and the number of grains per panicle increase under short-day conditions [39][40][41] ; however, tillering, which determines the number of panicles, is inhibited under short-day conditions. Consequently, the number of plantings at the transplanting site should be increased to compensate for reduced tillering and ensure that the required number of tillers is produced.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that vegetative growth could proceed relatively well, even when rice plants were grown under short-day conditions at a high temperature if the time of seeding and transplanting of younger seedlings was delayed. Panicle length and the number of grains per panicle increase under short-day conditions [39][40][41] ; however, tillering, which determines the number of panicles, is inhibited under short-day conditions. Consequently, the number of plantings at the transplanting site should be increased to compensate for reduced tillering and ensure that the required number of tillers is produced.…”
Section: Discussionmentioning
confidence: 99%
“…Late japonica rice lines, NK58, NK58s and NK58sr, reportedly showed responses to day length. No awns in panicles were observed under short-day conditions, but under long-day conditions, long awns protruded from the apices of lemmas [ 32 ]. The awns of progeny of the cross SLG × Nipponbare grown in Sanya during the present work were shorter than when the same materials were grown in Beijing.…”
Section: Discussionmentioning
confidence: 99%